Associations with low rates of postpartum glucose screening after gestational diabetes among Indigenous and non‐Indigenous Australian women - Catherine Chamberlain; Bronwyn Fredericks; Anna McLean; Brian Oldenburg; Jacqueline Mein; Rory Wolfe (Elsevier, 2015)
Abstract Objectives: To explore factors associated with postpartum glucose screening among women with Gestational Diabetes Mellitus (GDM). Methods: A retrospective study using linked records from women with GDM who gave birth at Cairns Hospital in Far North Queensland, Australia, from 1 January 2004 to 31 December 2010. Results: The rates of postpartum Oral Glucose Tolerance Test (OGTT) screening, while having increased significantly among both Indigenous* and non‐Indigenous women from 2004 to 2010 (HR 1.15 per year, 95%CI 1.08-1.22, p<0.0001), remain low, particularly among Indigenous women (10% versus 27%, respectively at six months postpartum). Indigenous women in Cairns had a longer time to postpartum OGTT than Indigenous women in remote areas (HR 0.58, 0.38-0.71, p=0.01). Non‐Indigenous women had a longer time to postpartum OGTT if they: were born in Australia (HR 0.76, 0.59-1.00, 0.05); were aged <25 years (HR 0.45, 0.23-0.89, p=0.02); had parity >5 (HR 0.33, 0.12-0.90, p=0.03); smoked (HR 0.48, 0.31-0.76, p=0.001); and did not breastfeed (HR 0.09, 0.01-0.64, p=0.02). Conclusions: Postpartum diabetes screening rates following GDM in Far North Queensland are low, particularly among Indigenous women, with lower rates seen in the regional centre; and among non‐Indigenous women with indicators of low socioeconomic status. Implications: Strategies are urgently needed to improve postpartum diabetes screening after GDM that reach women most at risk.